Double-blinded randomised placebo controlled trial of enterosgel (polymethylsiloxane polyhydrate) for the treatment of IBS with diarrhoea (IBS-D). Issue 12 (27th June 2022) - Howell, Carol Angela; Kemppinen, Anu; Allgar, Victoria; Dodd, Matthew; Knowles, Charles H; McLaughlin, John; Pandya, Preeti; Whorwell, Peter; Markaryan, Elena; Yiannakou, Yan
Abstract : Objective: Irritable bowel syndrome with diarrhoea (IBS-D) is a common and challenging condition that significantly reduces quality of life. Enterosgel (polymethylsiloxane polyhydrate) is an intestinal adsorbent which sequesters harmful molecules and is safe and effective in acute infective diarrhoea. This randomised controlled multicentre trial aimed to investigate its safety and efficacy in patients with IBS-D. Design: After a 2-week screening phase, participants were randomised into an 8-week double-blind phase, followed by an 8-week open-label and follow-up phase. Participants recorded stool consistency, pain and global symptoms in e-diaries and questionnaires. The primary outcome was the percentage of responders on a composite abdominal pain (≥30% decrease in the weekly score) and stool consistency (50% reduction in days per week with at least one stool of BSFS type 6 or 7) score during at least 4 weeks of the treatment period. Results: 440 patients with IBS-D were randomised to the double-blind phase with 393 continuing to the open-label phase. The Primary outcome responder rate by intention-to-treat for enterosgel versus placebo was 37.4% vs 24.3% (OR 1.95, NNT 8, p=0.002). Enterosgel also improved stool consistency (48.5% vs 32.5%, p<0.0001) abdominal pain (53.3% vs 40.2%, p=0.003), stool frequency (treatment effect −0.32 (−0.62 to −0.02)) and urgency (treatment effect −0.59 (−0.85 to −0.33)). 60% of patients reported adequate relief of symptoms after open-label treatment. Adverse event frequency was similar in both groups, with no serious events attributable to enterosgel. Conclusion: Enterosgel is safe and effective in IBS-D, providing an alternative to the limited current treatment options. Trial registration number: ISRCTN17149988 .